(3cTa GdeNOQGJ aj NHG GdeYTQGJs - (3eMeO Hf YHO GdhgGH Hf Ydj Hf GdLhGOs; (3GdTjN YHO GdZfjs
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdabjQ eMeO Hf YHOGdhgGH deG QCjJ eYTQGJ GdTjN GdYGQa YHOGdZfj fPQJ Cf CTQMgG s
(3BNQgG (B:s
(3QHfG JbHd efG Efc CfJ GdSejY GdYdje hJH YdjfG Efc CfJ GdJhGH GdQMje hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs